2018
DOI: 10.1093/mnras/sty2262
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for radial variations in the stellar mass-to-light ratio of massive galaxies from weak and strong lensing

Abstract: The Initial Mass Function (IMF) for massive galaxies can be constrained by combining stellar dynamics with strong gravitational lensing. However, this method is limited by degeneracies between the density profile of dark matter and the stellar mass-to-light ratio. In this work we reduce this degeneracy by combining weak lensing together with strong lensing and stellar kinematics. Our analysis is based on two galaxy samples: 45 strong lenses from the SLACS survey and 1,700 massive quiescent galaxies from the SD… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 72 publications
3
54
1
Order By: Relevance
“…Unlike substructures, we assume lineof-sight haloes to be located outside the virial radius of the lensing galaxy, that is, z los > z l + z vir or z los < z l − z vir , with z vir = 10 −3 (see Fig. 2 for theoretical results and Sonnenfeld et al 2018 for more details about the effects from the host stellar mass). Table 1.…”
Section: The Line-of-sight Halo Populationmentioning
confidence: 99%
“…Unlike substructures, we assume lineof-sight haloes to be located outside the virial radius of the lensing galaxy, that is, z los > z l + z vir or z los < z l − z vir , with z vir = 10 −3 (see Fig. 2 for theoretical results and Sonnenfeld et al 2018 for more details about the effects from the host stellar mass). Table 1.…”
Section: The Line-of-sight Halo Populationmentioning
confidence: 99%
“…The 'gradient strength' parameter K accounts for recent evidence of radial gradients in the central regions (< 0.4R e ) (e.g. van Dokkum et al 2017;Martín-Navarro et al 2015;Sonnenfeld et al 2018). We allow 0 ≤ K < 1.5 as this includes fully the range of gradient strengths reported in the literature.…”
Section: Model Parameterizationmentioning
confidence: 99%
“…HiM-50 ETGs have a much greater diversity in M/L, ranging from 1 to 5 below 0.3 re. These non-constant M/L ratios may have important consequences for dynamical mass measurements (see Bernardi et al 2018;Sonnenfeld et al 2018;Oldham & Auger 2018b), particularly when such masses are used to infer the IMF (Cappellari et al 2013b). Here we have shown that in the case of IMF variations, the assumption of a constant M/L within re is not justified.…”
Section: Radial Gradients In Stellar Population Propertiesmentioning
confidence: 99%